Initial Learning Experience for Electromagnetic Navigation Bronchoscopy: A Surgeon's Experience While Introducing the Navigation Technology in Pulmonary Lesion Diagnosis - Yuan-Ming Tsai; Yen-Shou Kuo; Ying-Yi Chen; Cheng-Hsi Yang; Yu-An Cheng; Hsu-Kai Huang (Journal of Medical Sciences, 2024)
Background: Diagnosing peripheral pulmonary lesions using a traditional bronchoscope is difficult. Reports on the learning experience for Veran's SPiN electromagnetic navigation bronchoscopy (ENB) for the diagnosis of pulmonary lesions are limited. Aim: We aimed to evaluate the skills developed by trainees who underwent Veran ENB learning in a clinical setting. Methods: We retrospectively examined the data of patients who had undergone Veran ENB to guide instruments through the airways to a target lesion for biopsy or localization from November 2019 to March 2022. Results: In total, 23 patients, including 16 with solid lesions (69.6%), 4 with pure ground-glass opacity (17.4%), and 3 with mixed (13.0%) were included. The median largest diameter of the pulmonary lesions was 2.7 ± 1.8 cm, whereas the median distance from the pleural surface to the edge of the pulmonary lesion in its shortest path was 1.9 ± 1.6 cm. Most lesions in this cohort had a positive air bronchus sign (69.6%). The mean procedure time for a young thoracic surgeon was longer after 10 cases of operation (45.6 ± 13.4 vs. 33.8 ± 9.2 min, P = 0.027). There were no complications reported related to the procedure. Conclusion: ENB is a safe and less invasive method for tissue diagnosis or preoperative localization for patients with pulmonary lesions. However, a young thoracic surgeon in the learning process requires more time to perform ENB. This study provides basic information about the learning experience of trainees while performing the ENB procedure.